Staging Anti-Inflammatory Therapy in Alzheimer's Disease - Galea, Elena (Frontiers in Aging Neuroscience, 2010)
The use of non steroidal anti-inflammatory drugs (NSAIDs) in Alzheimer´s disease (AD) is controversial because conclusions from numerous epidemiological studies reporting delayed onset of AD in NSAID users have not been corroborated in clinical trials. The purpose of this personal view is to revise the case for NSAIDs in AD therapeutics in light of: i) the last report from the only primary prevention trial in AD, ADAPT, which, although incomplete, points to significant protection in long-term naproxen users, and ii) the recently proposed dynamic model of AD evolution. The model contends that there is a clinical silent phase in AD that can last up to twenty years, the duration depending on life style habits, genetic factors or cognitive reserve. The failure of many purported disease-modifying drugs in AD clinical trials is forcing the view that treatments will only be efficacious if administered pre-clinically. Here we will argue that NSAIDs failed in clinical trials because they are disease-modifying drugs, and should be administered in early stages of the disease. A complete prevention trial in cognitively normal individuals is thus called for. Further, the shift of anti-inflammatory treatment to early stages uncovers a knowledge